Second Generation of Zafirlukast Derivatives with Improved Activity against the Oral Pathogen Porphyromonas gingivalis - Howard, Kaitlind C. (ACS Med Chem Lett, 2020)
[Image: see text] Porphyromonas gingivalis is a Gram-negative anaerobic pathogen that can trigger oral dysbiosis as an early event in the pathogenesis of periodontal disease. The FDA-approved drug zafirlukast (ZAF) was recently shown to display antibacterial activity against P. gingivalis. Here, 15 novel ZAF derivatives were synthesized and evaluated for their antibacterial activity against P. gingivalis and for their cytotoxic effects. Most derivatives displayed superior antibacterial activity against P. gingivalis compared to ZAF and its first generation derivatives along with little to no growth inhibition of other oral bacterial species. The most active compounds displayed bactericidal activity against P. gingivalis and less cytotoxicity than ZAF. The superior and selective antibacterial activity of ZAF derivatives against P. gingivalis along with an increased safety profile compared to ZAF suggest these new compounds, especially 14b and 14e, show promise as antibacterials for future studies aimed to test their potential for preventing/treating P. gingivalis-induced periodontal disease.